Tools for making acute risk decisions with chemical process safety applications. (Center for Chemical Process Safety of the American Institute of Chemical Engineers, 1995)
The complexity of today's risk decisions is well known. Beyond cost and risk there are many other factors contributing to these decisions, including type of risk (such as human injury or fatality), the economic impact on the local community, profitability, availability of capital, alternatives for reducing or eliminating the risk, costs of implementing alternatives, codes, standards, regulation, and good industry practice. This book presents a large range of decision aids for risk analysts and decision makers in industry so that vital decisions can be made in a more consistent, logical, and ri.
Keywords: Chemical plants -- Risk assessment.; elektronické knihy; electronic books